An improved SPH method for wave generation in free surface flow simulations - Ramli, Muhammad Zahir (2014)
eakeeping analysis involving violent ﬂows is still quite challenging because the conventional Reynolds averaged Navier-Stokes (RANS) approaches for complex numerical methods are not effective in such ﬂow simulations. This research aims to apply smoothed particle hydrodynamics (SPH), a fully Langrangian meshless method to investigate the behaviour of ships travelling in realistic waves. SPH has been used in a wide variety of hydrodynamic problems overcoming the limitation of ﬁnite volume/element type methods. It is capable of dealing with problems involving free surface ﬂows, deformable boundary and moving interface. This makes it a suitable alternative for simulating range of hydrodynamic problems, especially those involving severe ﬂow discontinuities, such as slamming, wave breaking and ﬂuid fragmentation, around complex hull-shapes, where the meshes tend to distort and, even, collapse completely.